2022
DOI: 10.1021/acs.joc.2c01282
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted Divergent Annulation of Conjugated Ynones and Methyl 2-(Cyanomethyl)benzoates to Access 1-Naphthols and Xanthones

Abstract: A facile and efficient base-mediated divergent annulation of methyl 2-(cyanomethyl)­benzoates and conjugated ynones has been described. A broad range of 1-naphthols and xanthones were formed in moderate to excellent yields. The notable features of this protocol include readily available precursors, broad substrate scope, complete regioselectivity, and substrate-controlled divergent synthesis. The gram-scale preparation and synthetic transformations of the resulting 1-naphthols and xanthones demonstrate their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…11 Later, this approach was further modified by Wang. 12 In 1993, Furukawa developed a method using dimethyl phthalide-3-phosphonates with various Michael acceptors, which led to the formation of naphthalene-1,4-diols. 13 Recently, Mal et al reported an annulation method based on the Michael–Dieckmann cascade reaction, in which the use of simple phthalides and acrylates afforded diversely substituted 1-naphthols.…”
Section: Introductionmentioning
confidence: 99%
“…11 Later, this approach was further modified by Wang. 12 In 1993, Furukawa developed a method using dimethyl phthalide-3-phosphonates with various Michael acceptors, which led to the formation of naphthalene-1,4-diols. 13 Recently, Mal et al reported an annulation method based on the Michael–Dieckmann cascade reaction, in which the use of simple phthalides and acrylates afforded diversely substituted 1-naphthols.…”
Section: Introductionmentioning
confidence: 99%
“…However, they need high temperature and oxidants or electrocatalysis. Inspired by our continuous interest in ynones chemistry, we envisioned that 3-acyl chromones may be conveniently synthesized from ynones with easily available methyl salicylates through a tandem [2 + 4] cyclization reaction under transition-metal-free conditions (Scheme c). Herein, we reported a simple and efficient route to synthesize 3-acyl chromones from ynones and methyl salicylates with high regioselectivity, broad substrate tolerance, and under mild and transition-metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature precedents ,, and control experiments, a plausible mechanism is depicted in Scheme for the reaction of 1a and 2a to give 3a via NHC-catalyzed intermolecular Stetter reaction–cyclization followed by aromatization. Carbene is generated by abstraction of a proton from NHC precatalyst B .…”
mentioning
confidence: 99%
“…The carbene adds to the aldehyde functionality of o -formylcinnamate 1a to give a tetrahedral intermediate I , which leads to the generation of Breslow intermediate II via 1,2 proton shift. Subsequently, the Breslow intermediate II undergoes an intermolecular conjugate addition to the β-position of ynone 2a to form an allene-type intermediate III . The enol moiety of the intermediate III undergoes intramolecular Michael addition to the α,β-unsaturated ester moiety (Michael acceptor) to form a cyclized intermediate IV with concomitant regeneration of the NHC.…”
mentioning
confidence: 99%